OsCUL3a Negatively Regulates Cell Death and Immunity by Degrading OsNPR1 in Rice. Issue 2 (18th January 2017) - Liu, Qunen; Ning, Yuese; Zhang, Yingxin; Yu, Ning; Zhao, Chunde; Zhan, Xiaodeng; Wu, Weixun; Chen, Daibo; Wei, Xiangjin; Wang, Guo-Liang; Cheng, Shihua; Cao, Liyong
Abstract : OsCUL3a interacts with and degrades OsNPR1 to regulate innate immunity in rice. Abstract: Cullin3-based RING E3 ubiquitin ligases (CRL3), composed of Cullin3 (CUL3), RBX1, and BTB proteins, are involved in plant immunity, but the function of CUL3 in the process is largely unknown. Here, we show that rice ( Oryza sativa ) OsCUL3a is important for the regulation of cell death and immunity. The rice lesion mimic mutant oscul3a displays a significant increase in the accumulation of flg22- and chitin-induced reactive oxygen species, and in pathogenesis-related gene expression as well as resistance to Magnaporthe oryzae and Xanthomonas oryzae pv oryzae. We cloned the OsCUL3a gene via a map-based strategy and found that the lesion mimic phenotype of oscul3a is associated with the early termination of OsCUL3a protein. Interaction assays showed that OsCUL3a interacts with both OsRBX1a and OsRBX1b to form a multisubunit CRL in rice. Strikingly, OsCUL3a interacts with and degrades OsNPR1, which acts as a positive regulator of cell death in rice. Accumulation of OsNPR1 protein is greater in the oscul3a mutant than in the wild type. Furthermore, the oscul3a osnpr1 double mutant does not exhibit the lesion mimic phenotype of the oscul3a mutant. Our data demonstrate that OsCUL3a negatively regulates cell death and immunity by degrading OsNPR1 in rice.